A consideration of the discoveries of gold and silver in the sixteenth century, with a view to point out the effects to be anticipated from the recent discoveries of gold. ? Silver proposed as a substitute for a gold standard, to prevent the anticipated rise in all prices to three times their former amount - Hancock, W. Neilson (Dublin Statistical Society, 1861)
The subject which I have selected to bring under your notice this evening is connected with one of the most remarkable events of our own day. The supply of gold and silver had remained at a regular and constant state for a period of about two centuries, when suddenly it was announced, in 1849, That gold had been discovered in enormous quantities in California; in two years California was eclipsed by New South Wales; in subsequent years there were successive discoveries in different parts of Australia, and the year before last a still more remarkable discovery led to the foundation of a new colony on the continent of North America, British Columbia.
Read Monday, February 28th 1861
Keywords: Gold standard; Silver standard; 314.15